When distance apart: The roles of emotional-social intelligence on trust among individuals engaging in long distance relationships - Ridhoi Meilona Purba; Margaret Khoman (Talenta Publisher, 2012)
We examined the role of emotional-social intelligence on trust, among couples engaging in long-termed long-distance romantic relationship (6 to 84 months), with meeting intensity between 1-12 times within a year. The results of this correlational study demonstrated that in general, individuals’ emotional intelligence predicted greater trust toward partner. However, the main component of emotional intelligence that predicted trust was not intrapersonal or interpersonal skills, but other emotional-social skills (stress management, adaptation, mood). Discussion was focused on the importance of each component of emotional-social intelligence on trust, among couples engaging in long-termed long-distance relationship.